Critical Analysis of Multidisciplinary Teams’ Impact on Patient Safety in Saudi Hospitals - ALSHEIKH, ESSA YASSEN ESSA; ALGARNI, MOIED AWAD MOHAMMAD; ALGHAMDI, NAIF SALEH AHMED; ALHARTHI, FAHAD ABDULRAHMAN; ALQAIMA, ABDULLAH ABDULRAHMAN; ALALWAN, ALWAN ABDULLAH AHMED; ALKHIWANI, ADEL ALI GANDAN; ALYAMI, TALAL AHMED SAUD; AL TAISAN, MANSOOR SALEH SAUD; HASHAISH, HUSSEIN MOHAMMED HUSSEIN BANI (Journal of Ecohumanism, 2024)
The delivery of healthcare in Saudi Arabia has undergone a transformation at some stages, with special emphasis on the use of MDTs in order to improve the safety of patients. In this paper, the author showcases a critical evaluation of the factors associated with patient safety enhancement in Saudi Arabian hospitals through MDTs concerning communication, role definition, and decision-making. Consistent with a mixed-methods approach, the study demonstrates the difficulties these teams encounter and how such difficulties affect safety processes, such as errors and patients’ satisfaction. Specific recommendations for enhancing MDT effectiveness are provided to reflect on Saudi Arabia’s Vision 2030 goals in healthcare.